Association of CAST2, HSP90AA1, DNAJA1 and HSPB1 genes with meat tenderness in Nellore cattle - Malheiros, Jessica Moraes [UNESP] (2018)
The objective of this study was to evaluate the association of expression of CAPN1, CAPN2, CAST, HSP90AA1, DNAJA1 and HSPB1 genes with meat tenderness in Nellore cattle. Three experimental groups were selected by shear force (SF): moderately tender (SF = 34.3 +/- 5.8 N), moderately tough (SF = 56.8 +/- 7.8 N), and very tough meat (SF = 80.4 +/- 15 N). Gene expression was evaluated by real-time PCR. Expression of the CAPN1, CAPN2, CAST and CAST1 genes did not differ between groups. Expression of the CAST2 was up-regulated (P < 0.05) in the moderately tough and very tough meat groups. Down-regulation of the HSP90AA1, DNAJA1 and HSPB1 genes (P < 0.05) was observed in the moderately tender meat group. The present results suggest that meat tenderness in Nellore cattle does not directly depend on the expression of the CAPN1 and CAPN2 genes, but is associated with the expression of other genes such as CAST2, HSP90AA1, DNAJA1 and HSPB1.